Alternative ring flange models for buckling verification of tubular steel wind turbine towers via advanced numerical analyses and comparison to code provisions. (January 2023) - Gantes, Charis J.; Koulatsou, Konstantina G.; Chondrogiannis, Kyriakos-Alexandros
Abstract: The beneficial effect of ring flanges between adjacent sections of tubular steel wind turbine t6owers to their susceptibility to local shell buckling is investigated by means of linear and nonlinear buckling finite element analyses, using alternative numerical models. Models comprising solid vs shell elements for the tower shell and solid vs shell vs beam elements for the ring flanges are compared, leading to similar results. Thus, computational cost is adopted as the deciding factor towards preferring the simpler and lighter models. Then, the behavior of an approximately 120 m tall wind turbine tower under realistic wind and gravity loads is investigated, focusing on the buckling response of successive configurations of sections of the tower below each flange, in order to assess the buckling potential throughout the tower height and compare to analytical buckling verification procedures proposed in EN1993-1-6. Nonlinear finite element analyses considering geometrical and material nonlinearity and imperfections with the shape of the three primary buckling modes are employed. The imperfection size is determined according to EN1993-1-6 for fabrication quality class A, B or C. Moreover, a parametric investigation of the thicknesses of ring flanges between consecutive tower sections indicates significant margins for thickness reduction in terms of the flanges' ability to act as stiffeners for preventing local buckling.